Influence of Solar Wind High‐Speed Streams on the Brazilian Low‐Latitude Ionosphere During the Descending Phase of Solar Cycle 24 - S. P. Moraes‐Santos; C. M. N. Cândido; F. Becker‐Guedes; B. Nava; V. Klausner; C. Borries; F. S. Chingarandi; T. O. Osanyin (Space Weather)
Abstract This study investigates the Brazilian low‐latitude ionospheric response to CIR/HSS‐driven geomagnetic storms during the declining phase of solar cycle 24, from 2016 to 2017. In this period the geomagnetic storms were mostly moderate, SymHmin ≈ −72 nT, AEmax ≈ 1580 nT, Vswmax ≈ 690 km/s and lasted, on average, for 6 days. We analyze the variations in Vertical Total Electron Content (VTEC) at three representative regions: bele, over the equatorial region; boav and cuib, at the northern and southern crests of the Equatorial Ionization Anomaly. Our findings reveal the role of High‐Speed Solar Wind Streams and Corotating Interaction Region—driven geomagnetic storms. The VTEC intensifications were up to 30 TECu, during the daytime and nighttime. Additionally, three categories of nighttime enhancements were observed and analyzed with distinct characteristics and levels of pre‐reversal strengthening; Depletions up to 20 TECu also occurred during the day and nighttime. The delay between the storm commencement and the positive and negative variations were, on average, 7 and 20 hours, respectively. We discuss the Prompt Penetration Electric Fields and Disturbance Dynamo Electric Fields following the magnetic reconnection between Earth's and interplanetary magnetic field, using observational data and modeling. Furthermore, this study presents catalogs of low‐latitude ionospheric storms, providing detailed information for space weather applications and ionospheric modeling.